Upaya Penanaman Nilai Pendidikan Multikultural pada Siswa Madrasah Ibtidaiyah - Rif'an Fauzi (MODELING: Jurnal Program Studi PGMI, 2017)
A multicultural country is a term that is suitable for Indonesia. Imagine, the diversity of religions and beliefs, even tribes scattered across more than 17,000 islands, the uniqueness of regional languages ​​which occupies the highest number in the world (more than 500 local languages) and a wide variety of other is the potential and uniqueness of the nation of Indonesia as a nation big. However, the diversity and uniqueness of this time did not get a place in the development process, especially in education. This study focuses on the efforts of growers value problems Multicultural education in madrasah students with a form of qualitative research in the madrasa Darul Falah Elementary Kandangan Kediri and multicultural value Planting result in madrasah Darul Falah dititiktekankan on Islamic Education learning process with methods appropriate to the students' development. and community involvement in the process of planting the value of multicultural students in the madrasah Darul Falah as part of efforts that are expected to contribute the maximum.